2014
DOI: 10.1186/1471-2407-14-271
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces apoptotic cell death of human cholangiocarcinoma cells through inhibition of myeloid cell leukemia-1

Abstract: BackgroundCholangiocarcinoma (CCA), a devastating neoplasm, is highly resistant to current chemotherapies. CCA cells frequently overexpress the antiapoptotic protein myeloid cell leukemia-1(Mcl-1), which is responsible for its extraordinary ability to evade cell death. Triptolide, a bioactive ingredient extracted from Chinese medicinal plant, has been shown to inhibit cell proliferation and induce apoptosis in several cancers.MethodsCCK-8 assay was performed to detect cell survival rate in vitro. DAPI staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…It has been documented that short hairpin RNA-mediated depletion of Mcl-1 enhanced the induction of cholangiocarcinoma cell apoptosis by the multikinase inhibitor BAY 43-9006 [27]. Triptolide, a bioactive ingredient extracted from the Chinese herb Tripterygium wolfordii Hook F, has been shown to cause apoptotic cell death of human cholangiocarcinoma cells through inhibition of Mcl-1 [28]. These studies indicate the important role for Mcl-1 in apoptosis resistance of cholangiocarcinoma cells.…”
Section: Discussionmentioning
confidence: 93%
“…It has been documented that short hairpin RNA-mediated depletion of Mcl-1 enhanced the induction of cholangiocarcinoma cell apoptosis by the multikinase inhibitor BAY 43-9006 [27]. Triptolide, a bioactive ingredient extracted from the Chinese herb Tripterygium wolfordii Hook F, has been shown to cause apoptotic cell death of human cholangiocarcinoma cells through inhibition of Mcl-1 [28]. These studies indicate the important role for Mcl-1 in apoptosis resistance of cholangiocarcinoma cells.…”
Section: Discussionmentioning
confidence: 93%
“…7) by ABT-263 in both HuCCT1 and HuH28 cell lines. Previous study has shown that the natural product Triptolide, the principle bioactive ingredient of the Chinese herb Tripterygium wilfordii Hook F, inhibited growth and downregulated MCL1 expression in CCA cells 29 . The results of western blotting validated the suppression of MCL1 by Triptolide in HuCCT1 and HuH28 cells (Fig.…”
Section: Genetic or Pharmacological Inhibition Of Mcl1 Sensitizes Ccamentioning
confidence: 96%
“…For instance, triptolide, a component of the Chinese herb Tripterygium wilfordii , is known to cause apoptosis in cancer cells [47]. Extracts of the herb have been used in clinical trials for a variety of inflammatory and immune-linked conditions, and have demonstrated both antiinflammatory and immune suppressant activity, raising concern for its effect on immune evasion [48,49].…”
Section: Methodsmentioning
confidence: 99%